Pragmatic comparative effectiveness study of multimodal fascia iliaca nerve block and continuous lumbar epidural-based protocols for periacetabular osteotomy. Issue 4 (26th February 2021) - Albertz, Megan; Whitlock, Patrick; Yang, Fang; Ding, Lili; Uchtman, Molly; Mecoli, Marc; Olbrecht, Vanessa; Moore, David; McCarthy, James; Chidambaran, Vidya
Abstract: Perioperative pain management protocols have a significant impact on early surgical outcomes and recovery. We hypothesized that multimodal protocol including fascia iliaca compartment nerve block (MM-FICNB) would decrease the length of hospital stay (LOS) by facilitating earlier mobilization, without compromising analgesia, compared to a traditional lumbar epidural-based protocol (EP). Demographics/comorbidities, surgical/block characteristics and perioperative pain/mobilization data were collected from a prospectively recruited MM-FICNB group ( N = 16) and a retrospective EP cohort ( N = 16) who underwent PAO using similar surgical techniques, physical therapy/discharge criteria. Association of MM-FICNB group with LOS (primary outcome), postoperative pain, postoperative opioid requirements in morphine equivalent rates (MER) (mcg/kg/h) and time to complete physical therapy were tested using multivariable and survival regression. Patient and surgical characteristics were similar between groups. Median time for FICNB performance was significantly less than epidural (6 versus 15 min; P < 0.001). LOS was significantly decreased in the MM-FICNB group (2.88 ± 0.72 days) compared to the EP group (4.38 ± 1.02 days); P < 0.001. MM-FICNB group had significantly lower MER on POD1 ( P = 0.006) and POD2 ( P < 0.001), with similar pain scores on all POD. MM-FICNB group was associated with decreased LOS and earlier mobilization ( P < 0.001) by covariate-adjusted multivariate regression. Cox proportional hazard regression model showed MM-FICNB subjects had 63 (95% CI 7–571, P < 0.001) times the chance of completing physical therapy goals, compared to EP. Compared to EP, MM-FICNB protocol allowed earlier mobilization and decreased post-surgical hospitalization by 1.5 days, without compromising analgesia, with important implications for value-based healthcare and cost-effectiveness.